Subjektivitas Perempuan dalam Cerpen âCenanaâ Karya Oka Rusmini - Rojak, Mohamad Abdul; Rahayu, Lina Meilinawati; Priyatna, Aquarini (JURNAL PESONA, 2017)
AbstractÂ This paper examines female subjectivity contained in the short-story "Cenana" by Oka Rusmini. This short story is part of a collection of short-stories "Sagra" which tells the efforts of female protagonists out of oppression patriarchal system. The method used in this research is feminist study. This study is based on the female subjectivity approach of Beauvoir reinterpreted by Tori Moi. The short-story of "Cenana" shows womens dominant issues in the depiction of womens experiences in an attempt to challenge the patriarchal system. The results of the analysis show that the female protagonist character is presented as a subjectivity that plays the body as an important role in its relation to male characters within the project of heterosexuality.Keyword: Oka Rusmini, female subjectivity, body, short-story.Â